2021
DOI: 10.5194/acp-2021-505
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Atmospheric composition in the European Arctic and 30 years of the Zeppelin Observatory, Ny-Ålesund

Abstract: Abstract. The Zeppelin Observatory (78.90° N, 11.88° E) is located on the Zeppelin Mountain at 472 m above sea level on Spitsbergen, the largest island of the Svalbard archipelago. Established in 1989, the observatory is part of the “Ny-Ålesund Research Station” and an important atmospheric measurement site, one of only a few in the high Arctic and as a part of several European and global monitoring programs and research infrastructures, notably the European Monitoring and Evaluation Programme (EMEP), the Arct… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 136 publications
(166 reference statements)
0
8
0
Order By: Relevance
“…The absence of a trend at the latter station is potentially due to the short time period investigated. For Zeppelin, Platt et al (2021) found a decline of 44 % between 1990 and 2019. The difference to findings by Hirdman et al (2010a) can be explained by the use of different data sets and seasonal vs. annual aggregates.…”
Section: Introductionmentioning
confidence: 98%
See 3 more Smart Citations
“…The absence of a trend at the latter station is potentially due to the short time period investigated. For Zeppelin, Platt et al (2021) found a decline of 44 % between 1990 and 2019. The difference to findings by Hirdman et al (2010a) can be explained by the use of different data sets and seasonal vs. annual aggregates.…”
Section: Introductionmentioning
confidence: 98%
“…Surface monitoring sites around the Arctic (Fig. 1) have been operated to determine air pollutants transported to the Arctic since as early as the 1960s at Kevo, Finland (Dutkiewicz et al, 2014;Yli-Tuomi et al, 2003b;Laing et al, 2014a); the 1970s at Barrow/Utqiaġvik, USA (Bodhaine and Dutton, 1993), and at Zeppelin, Ny-Ålesund Re-search Station (Platt et al, 2021); the 1980s at Alert, Canada (Sturges and Barrie, 1989); the 1990s at Villum Research Station, Greenland (Nguyen et al, 2016;Heidam et al, 1999); and more recently at a number of other observatories such as Summit, Greenland (Schmeisser et al, 2018); Tiksi, Russia (Asmi et al, 2016); Gruvebadet, Ny-Ålesund Research Station (Gilardoni et al, 2020;Traversi et al, 2021); Thule, Greenland (Becagli et al, 2019); and at Pallas, Finland (Aaltonen et al, 2006;Lohila et al, 2015). Observations at these stations cover a wide range of aerosol properties including their chemical composition, i.e., particulate sulfate (SO 2− 4 ), nitrate (NO − 3 ), ammonium (NH + 4 ), mainly based on filter collection and subsequent laboratory analysis, and optical properties such as scattering and absorption coefficients and derived equivalent black carbon (EBC) concentrations.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…In terms of socio-economic changes, impact of emissions from oil fields (e.g., Prudhoe Bay in Alaska), shipping (e.g., in Resolute Bay, Canada), flaring (e.g., in Siberia) and Arctic urban areas have been found to change aerosol composition as well as cloud properties (Kolesar et al, 2017;Aliabadi et al, 2015;Schmale et al, 2018;Gunsch et al, 2017). NssSO4 2can originate from the oxidation of DMS to SO2 and further to sulfuric acid (Hoffmann et al, 2016), which can then condense onto preexisting particles and contribute to cloud condensation nuclei or form new ones (Hodshire et al, 2019;Beck et al, 2020;Schmale and Baccarini, 2021;Park et al, 2021).…”
Section: Introductionmentioning
confidence: 99%